The Effect of the Problem-Based Learning Model on Students’ Critical Thinking Skills in IPAS Learning at SDN Lasoani - Isthifara Aulya; Herlina Herlina; Sisriawan Lapasere; Roberto Rolly Bulalong; Azizah Azizah (Journal of Educational Sciences, 2026)
This study aimed to determine the effect of the Problem-Based Learning model on the critical thinking skills of fourth grade students in IPAS learning at SDN Lasoani. The study employed a quantitative approach using a pre-experimental method with a one-group pretest and posttest design. The sample consisted of 26 fourth grade students selected through purposive sampling. Data were collected using essay tests developed based on Ennis’s critical thinking indicators and analyzed using descriptive statistics and the Wilcoxon Signed-Rank Test. The results showed that the mean score increased from 61.15 on the pretest to 82.31 on the posttest. Improvements were observed across all critical thinking indicators, with the highest increase found in the drawing conclusions indicator. The Wilcoxon Signed-Rank Test yielded a significance value of 0.001 (p < 0.05), indicating a significant difference between pretest and posttest scores. These findings demonstrate that the Problem-Based Learning model effectively improves students’ critical thinking skills through contextual problem-solving, investigation, discussion, and reflection activities. Therefore, PBL can be considered an effective instructional approach for enhancing critical thinking skills in IPAS learning within the context of the Merdeka Curriculum.